Doa dan Ketundukan kepada Allah SWT dalam Perspektif Al-Qur’an: Telaah QS. Al-Baqarah Ayat 186 dan 200–202 - Irpan Saputra Harahap; Edi Hermanto; M Hafiz; Tandi Cahyadi; Tiyo Nugraha (Jurnal Teologi Islam, 2026)
Prayer is a form of human devotion and submission to Allah SWT that encompasses theological, spiritual, psychological, and social dimensions. In the Qur’an, prayer is not merely understood as a request, but also as an act of worship that strengthens faith, nurtures reliance upon Allah (tawakkul), and shapes a Muslim’s character. This study aims to examine the meaning of prayer and submission to Allah SWT from the Qur’anic perspective, with particular focus on QS. Al-Baqarah verses 186 and 200–202. This research employs a qualitative approach using a library research method, with primary data sources consisting of the Qur’an, the Prophet’s hadith, classical and contemporary Qur’anic commentaries, as well as relevant scholarly literature. Data analysis is conducted through a descriptive-analytical method using a thematic tafsir (maudhu‘i) approach. The findings indicate that prayer functions as a means of strengthening faith and reliance on Allah, a medium of closeness (qurb) between servant and Creator, spiritual education, social cohesion, and guidance for maintaining balance between worldly life and the hereafter. In the context of contemporary Muslim life, prayer holds significant urgency as a spiritual foundation that fosters inner peace, optimism, and psychological resilience in facing the challenges of modern life.